Punishment in Latin America : explorations from the margins - Sozzo, Máximo; Dal Santo, Luiz (Perspectives on crime, law and justice in the Global South., 2024)
Challenging the Northern-centric approach that has dominated the literature on punishment-and-society, Punishment in Latin America draws on innovative theoretical perspectives to make sense of punishment, penal trends, institutions and practices in peripheral settings, taking Latin American countries as its case studies. Engaging with both historical trajectories and recent theoretical perspectives, contributors examine different aspects and dimensions of punishment and prison, identifying specific dynamics and features in a truly South-South conversation. Taking part in contemporary movements to decolonize, southernize and democratize criminology, the chapters focus on in-depth case studies covering Argentina, Brazil, Chile, Colombia, Ecuador, Peru, Uruguay and Venezuela, as well as wider, comparative analyses that go beyond country-specific contexts. Placing a critical emphasis on the insufficiency of Northern concepts and arguments to make sense of punishment within Latin America, the authors engage with these theories while at the same time avoiding a sense of subordination or dependency disconnected from their own contexts. Bringing together researchers working across Latin American, European and North American universities, this collection advances the southernization and decolonization of this field of knowledge.